2022
DOI: 10.2399/prn.22.0302013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality cases due to COVID-19 pandemic in a tertiary referral hospital

Abstract: Objective: This study aimed to report the clinical prognoses, laboratory findings, treatment procedures, and neonatal outcomes, from hospitalization to death, of Coronavirus Disease 2019 (COVID-19)-related cases of maternal mortality at our clinic. Methods: Fifteen cases of COVID-19-related maternal mortality, between April 2020 and October 2021, in the Department of Obstetrics & Gynecology of a Training and Research Hospital were retrospectively analyzed for the purpose of the study. Results: During the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Hantoushzadeh et al (15) reported that 77.77% of pregnant women with critical COVID-19 died. Tunç et al (16), demonstrated that all maternal deaths from COVID-19 infection involved reported symptoms of shortness of breath and cough upon initial hospital admission. The risk of maternal death was 1.27 times higher in the symptomatic group in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hantoushzadeh et al (15) reported that 77.77% of pregnant women with critical COVID-19 died. Tunç et al (16), demonstrated that all maternal deaths from COVID-19 infection involved reported symptoms of shortness of breath and cough upon initial hospital admission. The risk of maternal death was 1.27 times higher in the symptomatic group in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant individuals have been identified as a group requiring special attention in the context of COVID-19 owing to the immediate and potential long-term health considerations for both the mother and the unborn child (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, pregnant and control groups of the same age with COVID-19 were compared and observed that pregnancy does not increase the risk of SARS-CoV-2 infection but aggravates clinical outcomes (5). Due to the immune suppression status during pregnancy, more severe complications and death rates are observed as a result of SARS-CoV and MERS-CoV infections in pregnant women (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%